Penguatan Nilai Karakter Disiplin Melalui Penggunaan Buku Kendali Peserta Didik (Studi Kasus Di MAN 3 Blitar) - Izati, Nurun Naila; Sumarsono, Raden Bambang; Sobri, Ahmad Yusuf (Universitas Negeri Malang, 2023)
Abstract: This study aims to describe the use of control books to control student behavior in strengthening the value of disciplinary character, the role of teachers in stenghtening the value of disciplinary character, supporting and inhibiting factors along with solutions to inhibit program implementation. The research location is at MAN 3 Blitar. The research uses a qualitative approach with a case study method that discusses in detail and in depth related to the topic raised. Datacollection through observation, interviews and documentary studies. To obtain accurate data, researchers check the validity of data in the form of credibility tests, transferability tests, dependability tests, and confirmability tests. From the results of this study, it is known that MAN 3 Blitar places student control books as behavioral guidelines and references in assessing student personality. This program applies a system of violation points and enforcement on interdisciplinary students as well as awarding and appreciating disciplinary students. Teachers have an important role, namely as role models in behaving in accordance with the values of good disciplinary character and being supervisors of discipline, as well as being authorized to take action on interdisciplinary students. The supporters in the implementation of the discipline character strengthening program include 1) internal factors including: the vision and mission of the madrasah, the geographical location of the madrasah, cooperation of madrasah residents, madrasah culture and 2) external factors including: parental support, living environment, cooperation with madrasah partners. Meanwhile, obstacles to program implementation include: 1) Internal factors include: awareness of students, limited facilities and infrastructure, teacher professionalism, and 2) external factors, namely the economic background and family background of students. As a solution to overcome these obstacles, madrasah conducts student counseling, student visits, procurement of facilities and infrastructure, and coaching educators and education staff.Keywords: character value, discipline, control book, procedure, violationAbstrak: Penelitian ini bertujuan untuk mendeskripsikan prosedur penggunaan buku kendali, peran guru dalam menguatkan nilai karakter disiplin melalui penggunaan buku kendali, faktor pendukung dan penghambat beserta solusi penghambat pelaksanaan progam. Lokasi penenlitian berada di MAN 3 Blitar. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus yang membahas secara rinci dan mendalam terkait topik yang diangkat. Pengumpulan data melalui observasi, wawancara dan studi dokumenter. Untuk mendapatkan data yang akurat peneliti melakukan pengecekan keabhsahan data berupa uji kredibilitas, uji transferabilitas, uji dependabilitas, dan uji konfirmabilitas. Dari hasil penelitian ini diketahui MAN 3 Blitar menempatkan buku kendali peserta didik sebagai pedoman berperilaku dan acuan dalam penilaian kepribadian peserta didik. Pada program ini menerapkan sistem poin pelanggaran dan penindakan pada peserta didik indisipliner serta pemberian penghargaan dan apresiasi pada peserta didik disiplin. Guru memiliki peran penting yakni sebagai role model dalam berperilaku sesuai dengan nilai karakter disiplin yang baik dan menjadi pengawas kedisiplinan, serta berwenang untuk melakukan penindakan pada peserta didik indisipliner. Adapun pendukung pada pelaksanaan program penguatan nilai karakter disiplin meliputi 1) faktor internal antara lain: visi misi madrasah, letak geografis madrasah, kerja sama warga madrasah, budaya madrasah dan 2) faktor eksternal antara lain: dukungan orang tua, lingkungan tempat tinggal, kerja sama dengan mitra madrasah. Sedangkan penghambat pelaksanaan program meliputi: 1) faktor internal antara lain: kesadaran peserta didik, keterbatasan sarana dan prasarana, profesionalitas guru, dan 2) faktor ekstrenal yakni latar belakang ekonomi dan latar belakang keluarga peserta didik. Sebagai solusi untuk mengatasi kendala tersebut madrasah melakukan konseling peserta didik, kunjungan peserta didik, pangadaan sarana dan prasarana, serta pembinaan pendidik dan tenaga kependidikan.Kata kunci: nilai karakter, disiplin, buku kendali, prosedur, pelanggaran